Multi-Omics Analysis of Curculio dieckmanni (Coleoptera: Curculionidae) Larvae Reveals Host Responses to Steinernema carpocapsae Infection - Bin Wang; Fanyu Meng; Shiqi Song; Bin Xie; Shuxia Jia; Dongying Xiu; Xingpeng Li (Insects)
The hazelnut weevil larvae (Curculio dieckmanni) is a major pest of nut weevils, spending part of its life cycle in the soil and causing significant damage to hazelnut crops. Moreover, its concealed feeding behavior complicates effective control with chemical insecticides. The entomopathogenic nematode Steinernema carpocapsae, which efficiently kills weevil larvae, offers a promising biological control agent. To investigate the molecular responses of hazelnut weevil larvae to nematode infection, we employed integrated transcriptomic and proteomic analyses following infection by S. carpocapsae. Our results revealed substantial alterations in gene expression, particularly the upregulation of immune-related transcripts such as antimicrobial peptides (AMPs) and stress-responsive proteins like heat shock protein 70 (HSP70). Furthermore, significant metabolic reprogramming occurred, marked by the downregulation of carbohydrate metabolic pathways and activation of energy conservation mechanisms. Although we observed an overall correlation between mRNA and protein expression levels, notable discrepancies highlighted the critical roles of post-transcriptional and post-translational regulatory processes. Collectively, these findings advance our understanding of the molecular interaction between insect hosts and pathogenic nematodes and contribute valuable knowledge for enhancing the effectiveness of EPN-based pest management strategies.